MIGRAs: are they the new IGRAs? Development of monokine-amplified IFN-γγ release assays. (April 2012) - Kasprowicz, Victoria O; Halliday, John S; Mitchell, Jessica; Klenerman, Paul
IFN-γγ release by antigen-specific T cells can be used to track immune responses to infections and vaccines. In recent years, there have been substantial advances in the techniques available to measure IFN-γγ release and a generation of such assays are now available for clinical use, as well as in a research setting. Interferon release leads to subsequent release of interferon-responsive chemokines such as MIG and IP-10, thus amplifying the original signal. A number of investigators have assessed whether measurement of these chemokines might provide a sensitive platform for detection of infection and antigen-specific T-cell responses. In this article, we assess the potential of these new approaches. We have termed the new antigen-specific T-cell assays monokine-amplified IFN-γγ release assays (MIGRAs). Overall, it seems likely that improvements in the detection threshold could be made by analysis of antigen-triggered chemokines and potentially of other molecules in the future, although whether MIGRAs will provide additional clinical utility still remains to be determined.